2020
DOI: 10.1029/2020jb020309
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Conductivity of Ti‐Bearing Hydrous Olivine Aggregates at High Temperature and High Pressure

Abstract: We investigated the electrical conductivity of Ti-H-doped synthetic olivine aggregates at 4 GPa, 873-1273 K, and controlled oxygen fugacities. Under a given pressure and temperature, electrical conductivity depends on both hydrogen and Ti content, but these samples show different conductivity behavior from that observed in Ti-poor sample such as San Carlos olivine. We found that when Ti content is comparable to or larger than hydrogen content, Ti has notable effects on electrical conductivity, but the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 43 publications
0
15
1
Order By: Relevance
“…This will reduce of the concentration of (2𝐻) 𝑀𝑔 𝑋 and (4𝐻) 𝑆𝑖 𝑋 (Muir et al, Submittedb) and thus the conductivity even further. This is in contrast to measurements by Dai and Karato (2020) where it was found that Ti increases conductivity in water poor regions where {Ti Mg would have to diffuse quickly which we find to be unlikely so this is further evidence that the mechanism by which water increases conduction in olivine is not ionic diffusion.…”
Section: The Effect Of Mg Diffusion Rate Variations On Conductivitycontrasting
confidence: 99%
“…This will reduce of the concentration of (2𝐻) 𝑀𝑔 𝑋 and (4𝐻) 𝑆𝑖 𝑋 (Muir et al, Submittedb) and thus the conductivity even further. This is in contrast to measurements by Dai and Karato (2020) where it was found that Ti increases conductivity in water poor regions where {Ti Mg would have to diffuse quickly which we find to be unlikely so this is further evidence that the mechanism by which water increases conduction in olivine is not ionic diffusion.…”
Section: The Effect Of Mg Diffusion Rate Variations On Conductivitycontrasting
confidence: 99%
“…As usual, the relationship between the electrical conductivity of hydrous mineral and temperature satisfied with an Arrhenius relation, i.e., with the rise of temperature, and the electrical conductivity of sample will be increased, accordingly. As noted from a modified Arrhenius relation reported by Dai and Karato (2020) [9], the influences of water content and oxygen fugacity on the electrical conductivity of dry and hydrous Ti-doped polycrystalline olivine aggregates can be expressed as,…”
Section: Experimental Theory and Measurement Methodsmentioning
confidence: 99%
“…Recently, some available research found that the presence of water, either the trace molecular water (H2O) or the structural hydroxyl (OH) in hydrous mineral, plays a crucial role in many pressure-dependent physicochemical properties and their corresponding transport processes of deep Earth interior, such as electrical conductivity [9,10], elastic wave dispersion and its attenuation [11,12], grain-growth kinetics [13,14], elemental diffusion coefficient [15,16], dislocation creep [17,18], and dynamic recrystallization [19,20]. Whereas, the electrical conductivity of hydrous silicate minerals and rocks are highly sensitive to temperature, pressure, oxygen fugacity, crystallographic anisotropy, water-bearing content, dehydration effect, iron content, trace element of titanium-bearing content, oxidation-dehydrogenation effect, structural phase transition, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The electrical conductivities of geological samples at high temperatures and high pressures are required to invert the MT profiles. Numerous studies have therefore investigated the conductivity of the dominant geological materials in the Earth's interior (Reynard et al, 2011;Saltas et al, 2013Saltas et al, , 2020Manthilake et al, 2015Manthilake et al, , 2016Dai and Karato, 2020). Dehydration, metasomatism, and magmatism processes are considerably more active in subduction zones than in the stable continental lithosphere.…”
Section: Introductionmentioning
confidence: 99%
“…The Ol-NaCl-H 2 O system is therefore a relevant representation of the composition of wet regions in the uppermost mantle, e.g., mantle wedges of subduction zones. Although numerous studies have reported the high-pressure electrical conductivity of olivine single crystals and polycrystalline aggregates (Dai et al, 2010;Dai and Karato, 2014a;Dai and Karato, 2014b;Dai and Karato, 2014c;Dai and Karato, 2014d;Dai and Karato, 2020), the detailed Ol-NaCl-H 2 O system has not been previously reported under high-temperature and high-pressure conditions. In addition to the effects of pressure and oxygen fugacity, the molar percentages of magnesium and iron in synthetic olivine also exert a significant effect on the electrical conductivity of anhydrous samples at high temperatures and pressures (Dai and Karato, 2014b).…”
Section: Introductionmentioning
confidence: 99%